Lavender aromatherapy reduces menstrual pain intensity in adolescents: a double-blind randomized clinical trial - Made Tangkas; Mahadinata, Made; Artana, Adi; Rasti, Wida Maha (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2025)
Introduction: Before, during, or after a period, dysmenorrhea may occur. Menstrual discomfort may persist for one to several days throughout the menstrual cycle. The uterine muscles contracting to release endometrial tissue is believed to be the cause of colic or chronic discomfort. Some predisposing factors that play a role in the pathophysiology of primary dysmenorrhea have not been explained to date, it is suspected that prostaglandin factors are the main cause of perceived pain. There are two methods for treating menstruation pain: pharmaceutical and non-pharmacological. A non-pharmacological treatment that can give good results is the use of lavender aromatherapy because the content of essential substances in it is suspected to reduce anxiety and pain sensations to reduce the intensity of dysmenorrhea. Method: This study employs a double-blind, randomized pre- and post-test control design, thereby constituting a true experiment. This research was conducted in Susut Village, Bangli from January 2024 to March 2024. This study used a consecutive sampling technique followed by randomizing the grouping of treatment subjects who received the aroma of lavender therapy and the control subjects received a placebo for 15 minutes for 2 consecutive days. Pain intensity was measured using the NRS scale before and after the intervention. Results: This study involved 60 subjects consisting of 30 cases and 30 controls. The administration of lavender aroma therapy significantly reduced the intensity of dysmenorrhea pain compared to placebo. Conclusion: The administration of lavender aromatherapy lowers the intensity of dysmenorrhea pain.